Effects of the Wnt/β-Catenin Signaling Pathway on Proliferation and Apoptosis of Gastric Cancer Cells. (24th August 2022) - Chen, Jia; Wang, Xingyu; Zhang, Jianlin; Chang, Jiawei; Han, Chuanjun; Xu, Zhouwei; Yu, Hongzhu
Abstract : Objective . To explore the effect of the Wnt/ β -catenin signaling pathway on the proliferation and apoptosis of gastric cancer cells. Methods . An MTT colorimetric assay was used to detect the inhibitory effect of the Wnt/ β -catenin signaling pathway inhibitor FH535 on the proliferation of MKN45 gastric cancer cells. The cell proliferation index (PI) and apoptosis index (AI) were measured by flow cytometry. The expression levels of β -catenin, c-myc, and cleaved caspase-3 in MKN45 gastric cancer cells were detected. Results . After using the Wnt/ β -catenin signaling pathway inhibitor FH535, MKN45 gastric cancer cells showed obvious shrinkage, death, and cell density decrease. MTT showed that the A value of MKN45 gastric cancer cells in FH535 group was significantly lower than that in the control group (P < 0.05). The survival rate of MKN45 gastric cancer cells in FH535 group was significantly lower than that in the control group (P < 0.05). The cell cycle of gastric cancer was arrested in G 0/ G 1 phase. The expression levels of β -catenin and c-myc protein in MKN45 gastric cancer cells in FH535 group decreased significantly (P < 0.05), while the expression level of cleaved caspase-3 protein increased significantly (P < 0.05). Conclusion . The Wnt/ β -catenin signal molecule can maintain the proliferation of gastric cancer cells. Inhibition of the Wnt/ β -catenin signaling pathway can inhibit the proliferation of gastric cancer cells and promote the apoptosis of MKN45 gastric cancer cells.